Topology Optimization of an Engine Mounting Bracket - M.I.N, Ma'arof; H., Husain; J.B., Saedon; N.H.M, Nor; M.S., Meo; Girma, T. Chala; Muhammad, Abdul Wahab (International Journal of Emerging Technology and Advanced Engineering, 2022)
Engine mounting system is an essential component to a vehicle in providing the isolation of vibration and noise which are generated by the engine. While various system designs have been studied for improvements, less attention were given to study the effects of vibrational load to subcomponents of the mounting system – for example: the engine bracket. At high frequency working condition, the engine bracket may experience fatigue failure due to cumulative vibrational loading. Henceforth, any efforts to further reduce the structural weight of the said brackets may degrade its strength and this may lead to catastrophic result. This study aimed to enhance the mechanical property of an engine-mounting bracket with respect to cyclic load by means of weight-reduction topology optimization. An actual enginemounting bracket under vibrational load transmitted was modeled and analyzed using two different computer aided design software. An improved design of engine mounting bracket was modeled by reducing its total weight via the use of HyperWorks. In conclusion, this study has discovered an incremental of stress concentration area across the bracket when predetermined load is applied to the weight-reduced engine bracket